Gating of social reward by oxytocin in the ventral tegmental area - Hung, Lin W; Neuner, Sophie; Polepalli, Jai S; Beier, Kevin T; Wright, Matthew; Walsh, Jessica J; Lewis, Eastman M; Luo, Liqun; Deisseroth, Karl; Dölen, Gül; Malenka, Robert C (Science (American Association for the Advancement of Science), 2017)
The reward generated by social interactions is critical for promoting prosocial behaviors. Here we present evidence that oxytocin (OXT) release in the ventral tegmental area (VTA), a key node of the brain's reward circuitry, is necessary to elicit social reward. During social interactions, activity in paraventricular nucleus (PVN) OXT neurons increased. Direct activation of these neurons in the PVN or their terminals in the VTA enhanced prosocial behaviors. Conversely, inhibition of PVN OXT axon terminals in the VTA decreased social interactions. OXT increased excitatory drive onto reward-specific VTA dopamine (DA) neurons. These results demonstrate that OXT promotes prosocial behavior through direct effects on VTA DA neurons, thus providing mechanistic insight into how social interactions can generate rewarding experiences.